HGG-31. Unique case of a bithalamic H3K27-wildtype diffuse midline glioma, EGFR-altered with methylated MGMT. (3rd June 2022) - Reinecke, James; Cottrell, Catherine; Rush, Sarah; Judd, Alexis; Palmer, Joshua; Pierson, Christopher; Lazow, Margot; Wilson, Yelena
Abstract: BACKGROUND: Diffuse midline gliomas are aggressive pediatric brain tumors frequently associated with somatic mutations in histone genes H3F3A (H3.3) and HIST1H3B (H3.1), which promote gliomagenesis through reprograming of the epigenetic landscape by inhibiting the tri-methylation of H3K27 (H3K27-me3). H3K27M-mutant gliomas comprise over 80% of diffuse midline gliomas, and are characterized by dismal outcomes as well as near-ubiquitous absence of MGMT promoter methylation. The subset of H3K27-wildtype diffuse midline gliomas remains incompletely understood with regards to underlying pathogenesis, therapeutic targets, and prognosis. We present the clinical, imaging, histopathologic, and molecular characteristics of a pediatric patient with a bithalamic H3K27-wildtype diffuse midline glioma, EGFR-altered with methylated MGMT. CASE: A 10-year-old female presented with an infiltrative bithalamic T2-hyperintense mass lacking diffusion restriction or contrast enhancement on MRI. Initial pathological inspection from biopsy was consistent with high-grade neuroepithelial tumor favoring high-grade glioma, however, immunohistochemistry was negative for H3K27M and demonstrated reduced H3K27-me3. DNA sequencing uncovered mutations in EGFR (exon 20 insertion) and TP53 (R175H), with overexpression of EGFR and CDK6 (but not EZHIP ) identified by RNA-sequencing. Methylation profiling was consistent with high-grade glioma, matching closest with glioblastoma, IDH-wildtype, with positive MGMT promoter methylation. Treatment was initiated with focal chemoradiotherapy with concurrent temozolomide, with plans for adjuvant temozolomide/ lomustine.DISCUSSION: Our case adds to growing evidence suggesting bithalamic tumors represent a distinct genetic and epigenetic subset of diffuse midline gliomas often defined by H3K27-wildtype status, loss of H3K27-me3, and EGFR receptor alterations. Our patient's H3K27-wildtype, EGFR-altered tumor had reduced H3K27-me3 as well as positive MGMT promoter methylation, a molecular characteristic that has not been well-studied in H3K27-wildtype bithalamic gliomas, but is suspected to confer sensitivity to alkylating chemotherapy. The prevalence, prognostic impact, and therapeutic implications of MGMT promoter methylation in bithalamic H3K27-wildtype diffuse midline gliomas, including potential association with EGFR aberrations, requires further exploration.